When Do Employees Cyberloaf? An Interactionist Perspective Examining Personality, Justice, and Empowerment - Kim, Kwanghyun; del Carmen Triana, María; Chung, Kwiyoung; Oh, Nahyun (Human Resource Management, 2016)
Cyberloafing—using the Internet for non‐work‐related activities—is a prevalent counterproductive work behavior in the workplace, but researchers have not yet paid sufficient attention to this issue, especially related to the role of personality in cyberloafing. Recognizing such a research gap, and using a trait activation theory framework, this study examines whether conscientiousness and emotional stability negatively relate to cyberloafing. We further investigate how organizational justice perceptions and psychological empowerment moderate the negative relationship between these personality traits and cyberloafing. Based on a sample of 247 employees, we find that those high in conscientiousness cyberloaf less when they perceive greater levels of organizational justice. In addition, highly conscientious individuals cyberloaf less when they have low, rather than high, levels of psychological empowerment. Implications for research and practice as well as future research directions are discussed. © 2015 Wiley Periodicals, Inc.